MR Neurography: Pitfalls in Imaging and Interpretation - Andreisek, Gustav; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2015)
MR imaging of peripheral nerves, typically referred to as MR neurography, is a rapidly evolving technique that currently is drawing huge attention, both in research and in clinical settings. Both training and experience are necessary to detect the sometimes subtle findings and to avoid misinterpretation of abnormalities. This review article is intended to help radiologists with image evaluation and interpretation. Typical pitfalls are discussed as well as strategies to avoid them.
Keywords: MR neurography; diffusion tensor imaging; peripheral nerve; magnetic resonance imaging; neurography; neuropathy